2021
DOI: 10.12688/f1000research.73606.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of antiviral, antibiotic and immunomodulatory drugs in hospitalized COVID-19 patients: a retrospective study in Bandung, Indonesia

Abstract: Background: Evidence of highly effective repurposed drugs for coronavirus disease 2019 (COVID-19) is insufficient. However, empirical therapy using antiviral, antibiotic and immunomodulatory drugs is massive. Studies evaluating the clinical use of these drugs in Indonesia are sparse. Methods: We performed a retrospective study using medical records of hospitalized COVID-19 patients from July 2020 to March 2021 in Bandung, Indonesia. Data were collected at relevant timelines: age, sex, comorbid condition, perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Lie et al, reported not only the infectiveness of corticosteroids in declining the fever duration, hospitalization period, or the viral clearance time in the mild COVID-19 pneumonia corticosteroid-treated group (55 out of 475 patients) but their adverse effects in expanding the infection complications [172] . In their study, Muflihah et al, reported an increase in the mortality rate (six times) in patients subjected to immunomodulatory drugs (methylprednisolone and dexamethasone with tocilizumab) in their treatment regime compared to the untreated group [173] . On the other side, other studies related the delay in viral clearance upon corticosteroid administration in moderate-severe COVID-19 pneumonia to the age and health conditions of patients with nothing to do with early corticosteroid administration [174] .…”
Section: Current Drugs For Covid-19 Treatmentmentioning
confidence: 96%
“…Lie et al, reported not only the infectiveness of corticosteroids in declining the fever duration, hospitalization period, or the viral clearance time in the mild COVID-19 pneumonia corticosteroid-treated group (55 out of 475 patients) but their adverse effects in expanding the infection complications [172] . In their study, Muflihah et al, reported an increase in the mortality rate (six times) in patients subjected to immunomodulatory drugs (methylprednisolone and dexamethasone with tocilizumab) in their treatment regime compared to the untreated group [173] . On the other side, other studies related the delay in viral clearance upon corticosteroid administration in moderate-severe COVID-19 pneumonia to the age and health conditions of patients with nothing to do with early corticosteroid administration [174] .…”
Section: Current Drugs For Covid-19 Treatmentmentioning
confidence: 96%